Aktualisasi Prinisip The Right Man ini The Right Job Dalam Struktur Birokrasi Dinias Penanaman Modal Dan Pelayanan Terpadu Satu Pinitu Di Kabupaten Pangkajene Dan Kepulauan - Reliubun, Sasa Zainudin; Ismail, Imran; Juharni, Juharni (Paradigma Journal of Administration, 2023)
Penelitian bertujuan untuk menganalisis prinisip the right man n the right job Dinias penanaman modal dan  pelayanan terpadu satu pinitu di kabupaten pangkajene dan kepulauan, struktur birokrasi di dinias penanaman modal dan pelayanan terpadu satu pinitu di kabupaten pangkajene dan kepulauan, dan pengaruh prinisip the right man n the right job dalam struktur birokrasi pada dinias penanaman modal dan pelayanan terpadu satu pinitu di kabupaten pangkajene dan kepulauan. Jenis penelitian ni adalah kuantitatif dengan tipe penelitian expost facto. Data dikumpulkan dengan metode observasi, angket dan dokumentasi. Populasi dalam penelitian ni adalah keseluruhan pegawai yang bekerja di Dinias penanaman modal dan pelayanan terpadu satu pinitu di Kabupaten Pangkajene dan Kepulauan dan banyaknya sampel yaitu 28 orang. Hasil penelitian menunjukkan bahwa: (1) Prinisip The Right Man in The Right Job Dinias Penanaman Modal dan Pelayanan Terpadu Satu Pinitu di Kabupaten Pangkajene dan Kepulauan termasuk dalam kategori cukup, (2) Struktur Birokrasi di Dinias Penanaman Modal dan Pelayanan Terpadu Satu Pinitu di Kabupaten Pangkajene dan Kepulauan berada dalam kategori baik, (3) Terdapat Pengaruh Prinisip The Right Man in The Right Job dalam Struktur Birokrasi pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pinitu di Kabupaten Pangkajene dan Kepulauan. This study aimed to determine and analyze: (1) an overview of the principle of the right man in the right job investment service and one-stop integrated service in Pangkajene and Island regency, (2) an overview of the bureaucratic structure in the investment service and one-stop integrated services in Pangkajene and Island Regency, (3) the influence of the principle of the right man in the right job in the bureaucratic structure of the investment service and one-stop integrated service in Pangkajene and Islan Regency. This type of the study was quantitative with the type of expost facto study. Data was collected by observation, questionnaire and documentation methods. The population in this study were all employees who worked at the investment service and one-stop integrated service in Pangkajene and Island Regency and the number of sample was 28 people. The results of the study showed that: (1) The principle of The Right Man In The Right Job Investment Service and One-Stop Service in Pangkajene and Island Regency is included in the sufficient category, (2) Bureaucratic Structure in the investment service and one-stop integrated serviceiin the Pangkajene and  Island Regency is in the good category, (3) There is an Influence of The Right Man In The Right Job Principle in the Bureaucratic Structure of the Investment Service and One-Stop Integrated Service in Pangkajene and Island Regency.